ARTIFICIAL INTELLIGENCE; THE MONSTER OF POSTMODERN WORLD - Zara Khalid; Hareem Ahmad; Misbah Hafeez (International Journal of Contemporary Issues in Social Sciences, 2024)
With rapid technological advancement, human lives have been transformed; these advancements in artificial intelligence are our greatest existential threat as they have their disastrous outcome. This research article aims to explore the threats and challenges that the postmodern world is facing in the form of mechanical monsters of AI. It will explore the blurring of boundaries between natural intelligence and artificial intelligence through Derrida’s and Jameson’s concept of the ‘erasure of boundaries’; it will investigate how the phenomenon of excessive intervention of technology in every aspect of human lives is posing potential risks to mankind. This research is Qualitative Research where the content analysis of the postmodern fiction would be the main focus of the researchers. Frankenstein’s monster has proven to be a metaphor for new technology to show its disaster and movies like “I Robot” (2004), “A. I. Artificial Intelligence” (2001), “Ex Machina” (2014), and “Robot and Frank” (2012) question the definition of the “human identity”. The androids in the novel by Philip K. Dick in outward appearance are so humanlike that it causes fear among us. The disastrous effect of AI in postmodern fiction leads us to think about whether the technology is a monster or it is we; humans, who have made this technology disastrous.